2018
DOI: 10.18488/journal.61.2018.64.167.178
|View full text |Cite
|
Sign up to set email alerts
|

The Decline in Science Students’ Enrolment in Nigerian Colleges of Education: Causes and Remedies

Abstract: The article critically reviewed the decline in science students' enrolment in Nigerian Colleges of Education, causes and the solutions. The research evidence abounds that the students' enrolment for science education in the Nigeria colleges of education reduces every year. The causes for this drawback are the crux of this article. The Nigerian college of education is an institution saddled with the responsibility of training teachers for the primary and secondary schools. Nonetheless, the colleges had been cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…They added that the data are about the opinions, perceptions, views or feelings of individuals in the population. Other related studies [15], [33], [35], [36], [38] also adopted the descriptive survey as it was found to be the most applicable research design.…”
Section: Research Methods 21 Research Designmentioning
confidence: 99%
“…They added that the data are about the opinions, perceptions, views or feelings of individuals in the population. Other related studies [15], [33], [35], [36], [38] also adopted the descriptive survey as it was found to be the most applicable research design.…”
Section: Research Methods 21 Research Designmentioning
confidence: 99%
“…A study conducted in Nepal found that the returns to education are higher at the upper-secondary level and that the returns to education for women are greater than those for men (Dunusinghe, 2021). Thus, increasing girls' education opportunities contributes to reducing inequality, increasing decisionmaking potential, and strengthening economies (Kushiyait, 2010;Kola 2014;UNICEF, 2020).…”
Section: Why Invest In Girls' Education?mentioning
confidence: 99%
“…Wikipedia is a useful resource for building knowledge bases and is actively used in many areas (Zesch et al, 2007;Lehmannm et al, 2015;Rebele et al, 2016;Ponzetto and Strube, 2013;Mokhtar, 2017;Khan, Hassan, & Marimuthu, 2017;Garaeva and Ahmetzyanov, 2018;Kamau., Mwania and Njue, 2018;Aina and Ayodele, 2018;Audu, 2018;Promsri, 2018;Wang and Yang, 2018;Hassan and Kommers, 2018;Agbabiaka-Mustapha and Adebola, 2018). Zesch et al, (2007) developed a general purpose, high performance Java-based Wikipedia API to use Wikipedia as a lexical semantic resource in large-scale NLP tasks.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%